1997
DOI: 10.1183/09031936.97.10010133
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for diaphragmatic fatigue over the course of the night in obstructive sleep apnoea

Abstract: These findings do not support the development of diaphragmatic fatigue over the course of the night in obstructive sleep apnoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…However, other recent studies did not find any evidence of diaphragmatic muscle fatigue during sleep apnea. 30,31 The finding of a higher IME in OHS vs OSAS patients and the lack of relationship between PaCO2 and inspiratory muscle function suggests that a reduced IME is not a major determinant of daytime hypoventilation in OHS. Structural muscle changes could also contribute to inspiratory muscle dysfunction in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…However, other recent studies did not find any evidence of diaphragmatic muscle fatigue during sleep apnea. 30,31 The finding of a higher IME in OHS vs OSAS patients and the lack of relationship between PaCO2 and inspiratory muscle function suggests that a reduced IME is not a major determinant of daytime hypoventilation in OHS. Structural muscle changes could also contribute to inspiratory muscle dysfunction in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this hypothesis, GRIGGS et al [22] reported a prolonged relaxation rate of inspiratory muscle in patients with sleep apnoea. In contrast, MONTSERRAT et al [21] and CIBELLA et al [24], using the technique of diaphragm EMG frequency analysis, were unable arterial oxygen saturation (Sa,O2). End-expiratory Poes increased gradually over the course of an apnoea.…”
Section: Significance Of the Findingsmentioning
confidence: 94%
“…It is usually considered that, at least during nonrapid eye movement sleep, the respiratory muscles, including the diaphragm, work hard to overcome upper airway resistance based on the observation that Poes swings increase during OSA episodes and fall during arousal [21]. Indeed, some investigators have hypothesised that respiratory muscle fatigue would occur in patients with severe OSA [22,23].…”
Section: Significance Of the Findingsmentioning
confidence: 99%
“…GRIGGS et al [4] have shown that pleural pressure relaxation rates during voluntary sniff maneuvers were prolonged in the morning compared with the preceding night prior to sleep in OSA patients. However, MONTSERRANT et al [5] reported lack of evidence for diaphragmatic fatigue during the night in these patients. They explained that the fatiguing levels of inspiratory effort generated throughout the night did not continue for sufficiently long periods to develop impaired contractility.…”
mentioning
confidence: 85%
“…The chronic overuse of the diaphragm was reported to put OSA subjects at risk of inspiratory muscles fatigue [3]. However, whether diaphragm fatigue actually occurs in OSA patients is still controversial [4][5][6]. GRIGGS et al [4] have shown that pleural pressure relaxation rates during voluntary sniff maneuvers were prolonged in the morning compared with the preceding night prior to sleep in OSA patients.…”
mentioning
confidence: 99%